Thirty-two years of inequality in coaching at the FIFA Women`s World Cup (1991-2023): do gender, race and region matter? - Lima Sampaio, M. E.; Barreira, J. (Soccer & Society, 2026)
This study examines gender, race, and regional representation among head coaches in all editions of the FIFA Women`s World Cup (1991-2023). Using a quantitative, longitudinal design, data were collected from official tournament records and analysed descriptively. Results revealed that women represented only 24% of all head coaches, with even lower proportions for women of colour and coaches from the Global South. Despite limited access, women coaches achieved disproportionately high success, winning 44% of the titles. Additionally, women were more likely than men to return for multiple editions, suggesting strong performance when given the opportunity. These findings challenge persistent stereotypes about leadership competence and masculinity in sport. The study highlights the need for equity-driven policies in coaching recruitment and retention, particularly for underrepresented groups. It contributes to ongoing debates on gender and performance, calling for structural change to ensure fair access to leadership in women`s football.